'Direct democratic institutions': direct and democratic?. (3rd July 2019) - Barreyro, María Emilia
ABSTRACT: The manuscript offers a theoretical reflection on the concept of direct democratic institutions with the aim of shedding light on their institutional grammar. Specifically, it addresses the two most relevant features attributed to them, namely, their direct nature and their democratic legitimacy. Referendums, citizens' initiatives, agenda initiatives and recall procedures, the four law-making mechanisms to which the concept of 'direct democratic institutions' in the strict sense refers, are said to be political processes in which 'the law of the land is made by citizens firsthand'. In addition, they seem to enjoy an undeniable democratic legitimacy. The paper argues against positions that hold that these institutions have in fact no direct nature at all and engages in the debate about their democratic legitimacy, starting from the assumption that they are not inherently democratic just because they measure the will of the people through popular votes.